Passage kinetics of digesta in horses fed with coastcross hay ground to different degrees - Silva,Vinicius Pimentel (2014)
This study was conducted to evaluate the kinetics, physicochemical characteristics and particle size of digesta in the right ventral colon (RVC) of horses fed coastcross hay ground to different degrees. Four horses fitted with cannulae in the RVC were used and were fed the following forms of hay: long, chopped, ground to 5 mm and ground to 3 mm. A Latin Square 4x4 study design was used. Each experimental period included 10 days for diet adaptation, four days for feces collection and one day for digesta collection. The kinetics of the particulate and solute phases of digesta were evaluated based on the mean retention time (MRT), passage rate (k) and transit time (TT) using two external markers: Cr-NDF and Co-EDTA. The TT of solid phase digesta was 3 hours longer (P<0.05) for ground hay than with the other physical forms of hay. There was no difference (P>0.05) in k or MRT in either the liquid or solid phase of digesta as a function of the different degrees of hay grinding. However, the liquid phase of digesta presented a higher k than the solid phase, with values of 3.28 and 2.73 h-1 being obtained, respectively. The smallest particle size and the lowest neutral detergent fiber contents in colon digesta were observed when hay ground to 3 mm was offered, leading to values of 0.51 mm and 53.46%, respectively. Grinding the hay increased the transit time of the liquid phase in the digestive tract of the horses, whereas no change in the kinetics of the solid phase digesta was observed. The grinding of hay reduced the NDF and the average particle size in the right ventral colon.